ACOUSTIC EMISSION AT TREATING TOOL WEAR WITH A NOT CONTROLLED CUTTING DEPTH - Filonenko, Sergii (Proceedings of National Aviation University, 2017)
Purpose: The aim of this article is to research of acoustic emission at composite material machining with not controlled cutting depth and cutting tool from composite material wear. Methods: In the basis of researches lies the simulation acoustic radiation, which appears at destruction of treated composite material surface layer and treating tool wear. The case of prevailing treated composite material mechanical destruction surface layer was esteemed, and tool wear descends without change of cutting depth. The statistical processing of acoustic emission amplitude parameters for want and originating treating composite material wear was conducted. The analysis of acoustic emission amplitude parameters legitimacies change, and as their sensitivity to treating composite material wear at not controlled machining depth was conducted. Results: Is determined, that the ascending of treating composite material wear is accompanied by decreasing of acoustic emission statistical amplitude parameters - amplitude average level, its standard deviation and dispersion. Are obtained of acoustic emission amplitude parameters regularity decreasing at increasing of treating composite material wears. The acoustic emission amplitude parameters percentage decreasing at ascending of treating composite material wear, in relation to their values without tool wear is determined. It is shown, that the decreasing of acoustic emission amplitude average level dispersion advances decreasing of amplitude average level and its standard deviation. Discussion: The simulation of acoustic radiation at prevailing mechanical destruction treated composite material surface layer with a not controlled cutting depth and treating composite material wear is conducted. It is shown, that the ascending of tool wear results in decreasing acoustic radiation statistical amplitude parameters. Is determined, that decreasing of acoustic emission signals amplitude average level dispersion advances decreasing of amplitude average level and its standard deviation. The decreasing of acoustic radiation amplitude average level and its spread values is conditioned by the different contribution of acoustic emission signals components, which appears at treated material destruction and treating composite material wear. Apparently, that at decreasing of treated composite material area destruction the arising signals amplitude parameters decreasing advances ascending of signals amplitude parameters, which appear at increase of treating composite material wear. The outcomes of the conducted researches can be used at mining of cutting tool condition verification methods and control of technological process machining parameters. These methods are of interest in the robotic technological processes, the monitoring and control by which one is possible for conducting through neuronal networks.